ATP-binding cassette transporter subfamily C members 2, 3 and cadherin protein are susceptibility-determining factors in Bombyx mori for multiple Bacillus thuringiensis Cry1 toxins. (December 2021) - Wang, Yonghao; Adegawa, Satomi; Miyamoto, Kazuhisa; Takasu, Yoko; Iizuka, Tetsuya; Wada, Sanae; Mang, Dingze; Li, Xiaoyi; Kim, Seungwon; Sato, Ryoichi; Watanabe, Kenji
Abstract: Field-evolved resistance of insect pests to Bacillus thuringiensis (Bt) toxins (Cry toxins) is a threat to the efficacy of Bt-based bio-insecticides and transgenic crops. Recent reports have suggested that ATP-binding cassette transporter subfamily C2 (ABCC2) and cadherin-like receptor play important roles in conferring susceptibility to Cry1 toxins. However, the receptors involved in Bt susceptibility in each insect remain unclear. To determine the receptors that are involved in the susceptibility of Bombyx mori to Cry1 toxins (1Ab, 1Ac and 1Fa), we conducted diet overlay bioassay using B. mori strains disrupted with one or two receptor (s) among BmABCC2, BmABCC3, and cadherin-like receptor (BtR175) generated by transcription activator-like effector nuclease (TALEN)-mediated gene editing. The single-knockout strains for BmABCC2 showed resistance to Cry1Ab and Cry1Ac, whereas only strains with double knockout of BmABCC2 and BmABCC3 exhibited high resistance to Cry1Fa. Progeny populations generated from the crossing of heterozygotes for BtR175 knockout allele included 25% theoretical homozygotes for the BtR175 knockout allele and they showed resistance to Cry1Ab and Cry1Ac. Then, through a cell swelling assay using Sf9 cells ectopically expressing the receptor, we analyzed the mechanisms underlying the different contributions of BmABCC2, BmABCC3, and BtR175 to larval susceptibility. The receptor activity of BmABCC2 for Cry1Ab and Cry1Ac was far higher than that of BmABCC3, and BtR175 synergistically enhanced the receptor activity of BmABCC2. This result well explained the important involvement of BmABCC2 and BtR175 in the larval susceptibility to Cry1A toxins. By contrast, the receptor activities of BmABCC2 and BmABCC3 for Cry1Fa were observed at a similar level and synergistic effect of BtR175 was small. This finding explains the equal importance of BmABCC2 and BmABCC3 and very small contribution of BtR175 on larval susceptibility to Cry1Fa. Thus, we demonstrated the different importance of BmABCC2, BmABCC3, and BtR175 to various Cry1 toxins as susceptibility-determining factors in B . mori larvae and the underlying basis for the observed differences. Furthermore, a weak correlation was indicated between the binding affinity and receptor activities of BmABCC2 and BmABCC3 to Cry1 toxins. Graphical abstract: Image 1 Highlights: BmABCC2, -3, and BmCadherin may be determinants of Cry1Ab, Ac and Fa susceptibility in B. mori. BmABCC2 has higher receptor function than BmABCC3 for Cry1Ab and Ac but not for Fa. Receptor activities of BmABCC2 and 3 can be enhanced by synergism with BmCadherin for Cry1Ab and Ac. Binding affinities to Cry1s are correlated with receptor activity of BmABCC2 and 3.